Terapi Naratif untuk Mengobati Depresi Mahasiswa: Laporan Kasus - Swasti, Idei Khurnia (INSAN Jurnal Psikologi dan Kesehatan Mental, 2024)
In the context of college students' depression, narrative therapy is beneficial to explore and challenge negative self-perceptions and beliefs contributing to their depressive symptoms. Narrative therapy was conducted through telecounseling using a video-conference platform with nine sessions for a female university student in her mid-20s with depressive mood, low energy, and suicidal thoughts, resulting in delays in her academic task fulfillment. She hardly finished her fieldwork reports and had not started her thesis after receiving a study period extension when majority of her classmates had graduated. The intervention was aimed to change client's depression narrative to more empowered preferred stories shaping her new identity so she could graduate from her program. During the  the intervention process, the participant can finish her academic obligations and graduate before the due date. Discussion about the case is provided for practitioners interested in the narrative approach, supported by the worksheets and therapy stages explanation.